OPINIONS OF MEDICAL FACULTY STUDENTS ON THE RATIONALITY OF USING TRADITIONAL MEDICINE FOR THE TREATMENT OF ONCOLOGICAL DISEASES (American Journal of Interdisciplinary Research and Development, 2024)
During the training of students at the medical faculty, future doctors should develop professional thinking based on the principles of evidence-based medicine. To understand to what extent medical students are inclined to be guided by these principles when choosing treatment, a survey was conducted, including a question about the rationality of using various traditional medicine for the treatment of oncological diseases.